2001
DOI: 10.1002/pen.10862
|View full text |Cite
|
Sign up to set email alerts
|

On‐line measurement of polymer orientation using ultrasonic technology

Abstract: The propagation velocity of an ultrasonic shear wave can be used to detect anisotropic behavior in the mechanical properties of a solid. Thus, an ultrasonic shear transducer imbedded in an injection mold produces a signal that is sensitive to polymer orientation. This results in a non‐invasive, on‐line technique for monitoring the orientation of polymer in an injection mold cavity during part cooling and solidification. The technique is shown to be quite sensitive for semicrystalline polymers, but much less ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 5 publications
0
20
0
Order By: Relevance
“…That is, when HDPE forms the matrix, HDPE chains are oriented along flow direction and when iPP forms the matrix, iPP chains in parent lamella are oriented along flow direction while chains in daughter lamella are perpendicular to flow direction. The remaining question is how we understand that V p is always lower than V v in oriented HDPE matrix, which is contrary to the propagation behavior in oriented LDPE sample [19]. A very low crystallinity and orientation exists in oriented LDPE due to its highly branched structure.…”
Section: Discussionmentioning
confidence: 83%
See 2 more Smart Citations
“…That is, when HDPE forms the matrix, HDPE chains are oriented along flow direction and when iPP forms the matrix, iPP chains in parent lamella are oriented along flow direction while chains in daughter lamella are perpendicular to flow direction. The remaining question is how we understand that V p is always lower than V v in oriented HDPE matrix, which is contrary to the propagation behavior in oriented LDPE sample [19]. A very low crystallinity and orientation exists in oriented LDPE due to its highly branched structure.…”
Section: Discussionmentioning
confidence: 83%
“…Edwards et al used tensile property to verify the ultrasound data and some conflicts between the ultrasound data and tensile strength was mentioned in Ref. [19]. In our work, since PP and HDPE are crystalline, 2D-WAXS was preferentially chosen for comparison, and the consistency of the ultrasound data with 2D-WAXS was observed.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…[76][77][78][79][80] It was reported that ultrasonic sensors had been employed to investigate a wide range of process characteristics such as the melting behavior of the resin in the injection barrel, temperature and pressure variation in the nozzle, melt-front flow inside the cavity, cavity pressure, solidification behavior in the cavity, polymer orientation, and some quality responses such as part dimension.…”
Section: Mold Separation Controlmentioning
confidence: 99%
“…These are off-line methods and cannot provide a continuous observation on the sample during melt deformation. The degree of orientation of injectionmolded parts at the solidification stage has been studied by using ultrasonic shear wave transducers [16,17]. Again, the method only applies to solid samples.…”
Section: Introductionmentioning
confidence: 99%